Cardiac troponins in young marathon runners - Traiperm, N.; Gatterer, H.; Wille, M.; Burtscher, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Increases of troponins have been shown to be relatively common among adult marathon finishers with levels typically diagnosed in acute myocardial infarction (Fortescue EB et al., 2007). Especially less marathon experience and younger age seem to be associated with more pronounced elevations of serum troponins (Tian Y et al., 2006). Data on adolescent runners have only been reported for prolonged running in laboratory-based settings and after 21 km running (Fu F et al., 2009, Tian Yet al., 2006, Nie J et al., Frank H Fu et al., 2010) and are practically missing for a whole marathon distance. Therefore, the aim of this study was to investigate cardiac troponins in young marathon runners of both sexes. Methods: Forty young Asian runners (20 healthy males and 20 females) aged between 13-17 years participated in this study. Blood samples were taken before, immediately after and 24 hours after a standard marathon race for determination of cardiac troponin T and troponin I. All participants had to undergo a routine physical examination, electrocardiogram (ECG) and provided a detailed training history. The experimental protocol was approved by the Khon Kaen University Ethics Committee for Human Research, and was performed as a PhD thesis at the Department of Sport Science of the University of Innsbruck. Results: Thirty seven runners completed the race. In 30 out of 37 participants the levels of troponin T and/or troponin I exceeded the upper reference limit of 0.01 and 0.1 ng/mL immediately after the race and in 3 participants these levels were even higher than the reference range for acute myocardial infarction (>0.1 ng/mL and >0.5 ng/mL for troponin T and I, respectively). Twenty four hours after the marathon troponin levels of all participants returned below the upper reference limit. Troponin T values of male participants were negatively related to their training history (35±15 months of training). Discussion: These findings imply also for young runners that elevated cardiac troponin levels after finishing a single marathon might rather be a physiological than a pathological response and that a preceding long period of regular running may be protective at least in young male runners.